Associação entre presença de Mycoplasma hominis e Ureaplasma urealyticum e níveis de citocinas pró e antiinflamatórias no líquido amniótico de gestação de termo - Ramos, Bruna Ribeiro de Andrade [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Microbial invasion of the amniotic cavity has been described in term deliveries and its role on the immune modulation is of interest to the better understanding of the underlying labor processes. The aim of this study was to determine the prevalence of Mycoplasma hominis and Ureaplasma urealyticum in the amniotic fluid of term pregnancies and to evaluate its influence on cytokines production at the end of pregnancy. A cross sectional study was conducted with fifty five pregnant women out of labor with intact membranes and gestational age between 37 and 41 weeks seen at the Bom Jesus hospital in Ariquemes, Rondônia, between June 2009 and May 2010. Amniotic fluid samples and fragments of chorioamniotic membranes were collected at cesarean section. M. hominis and U. urealyticum detection was performed by PCR and Interleukin (IL)-1β, IL-6, IL-8, IL-10 and Tumor Necrosis Factor (TNF)- levels were determined by ELISA. Chorioamniotic membranes were submitted to histopatological analyses. Presence of M. hominis was detected in 36.4% of amniotic fluid samples and any of them was positive for U. urealyticum. Regarding cytokines levels, 63.6% and 90.9% of samples have not shown detectable concentrations of TNF- and IL-1β. The median concentration of IL-6 and IL-8 were 107.9 pg/mL (0-517.1) and 208.1 pg/mL (0-1897.4), respectively. Interleukin-1, IL-6, IL-8 and TNF- concentrations were not associated with the presence of M. hominis in amniotic fluid, regardless the gestational age. No sample had detectable IL-10 levels. The histopatological analyses have shown no chorioamnionitis in any of the membranes, only a discreet mononuclear infiltration in the decidua could be observed in 40.4% of the samples. Presence of M. hominis was detected in 36.4% of amniotic fluid samples and any of them was positive for U. urealyticum. Regarding cytokines levels, 63.6% and 90.9% of samples have not... (Complete abstact click electronic access below)
Keywords: Gravidez; Líquido amniótico; Mycoplasma hominis; Term pregnancies; Amniotic fluid; Pro-inflammatory cytokines